Dual role of Nrf2 signaling in hepatocellular carcinoma: promoting development, immune evasion, and therapeutic challenges - Gan, Lin; Wang, Wei; Jiang, Jinxiu; Tian, Ke; Liu, Wei; Cao, Zhumin (Frontiers in Immunology, 2024)
Hepatocellular carcinoma (HCC) is the predominant form of liver cancer and ranks as the third leading cause of cancer-related mortality globally. The liver performs a wide range of tasks and is the primary organ responsible for metabolizing harmful substances and foreign compounds. Oxidative stress has a crucial role in growth and improvement of hepatocellular carcinoma (HCC). Nuclear factor erythroid 2 [1]-related factor 2 (Nrf2) is an element that regulates transcription located in the cytoplasm. It controls the balance of redox reactions by stimulating the expression of many genes that depend on antioxidant response elements. Nrf2 has contrasting functions in the normal, healthy liver and HCC. In the normal liver, Nrf2 provides advantageous benefits, while in HCC it promotes harmful effects that support the growth and survival of HCC. Continuous activation of Nrf2 has been detected in HCC and promotes its advancement and aggressiveness. In addition, Activation of Nrf2 may lead to immune evasion, weakening the immune cells' ability to attack tumors and thereby promoting tumor development. Furthermore, chemoresistance in HCC, which is considered a form of stress response to chemotherapy medications, significantly impedes the effectiveness of HCC treatment. Stress management is typically accomplished by activating specific signal pathways and chemical variables. One important element in the creation of chemoresistance in HCC is nuclear factor-E2-related factor 2 (Nrf2). Nrf2 is a transcription factor that regulates the activation and production of a group of genes that encode proteins responsible for protecting cells from damage. This occurs through the Nrf2/ARE pathway, which is a crucial mechanism for combating oxidative stress within cells.